Chance of revolts and ability of oppressions: a comment on the Acemoglu-Robinson model - Tetsuya Saito (Kiel Institute for the World Economy (IfW), 2010)
In the original framework of Professors Acemoglu and Robinson, the government is unable to oppress the revolution once it is brought about. However, actual civil wars are unpredictable. With this notion, I introduce uncertainty depending on military expenditures of the government. Then an interesting argument follows: if the likelihood of successful oppression is sufficiently larger than a certain level of destruction rate and there are cheap-but-effective devices such as biochemicals, citizens in a dictatorial country may have a trade-off between economic prosperity and domestic military threats.
Keywords: C72; H56; 330; Military expenditures; Acemoglu-Robinson model; war of attrition